Evaluasi Kebijakan Sosial di Daerah Tertinggal Kabupaten Nias Barat - Undang, Gunawan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Social policy evaluation in West Nias Regency is important, considering the phenomenon shows that the district is still a disadvantaged area, experiencing budget political inequality, and lack of governance innovation. This article aims to evaluate the problem from the social demension and social policy dimensions. This study uses a qualitative descriptive method with data sources from the Ministry of Home Affairs of the Republic of Indonesia (Ministry of Home Affairs of the Republic of Indonesia, 2023) and the Central Statistics Agency (BPS, 2023) as well as the results of previous research. The results of the study show that the evaluation of social policies in West Nias Regency – as a disadvantaged area – can be seen from the social dimension and the social policy dimension: (1) From the social dimension, it is important to prioritize equity and justice considering that there is still a high disparity in budget allocation and is below the provincial average, with the lowest Regional Original Revenue (PAD), Transfer Funds, Other Revenues, and Regional Budget (2022). PAD's contribution to the regional budget is only 2%. However, internally, this district has been relatively able to improve its social problems, winning the Innovative Government Awards (IGA Awards) in the category of Innovative Disadvantaged Areas (2022); and (2) from the social policy dimension, this district is important to innovate, such as local governance innovation and public service innovation with the target of developing government service digitalization activities; poverty alleviation; ease of investment; and stability, security and social life. The novelty of this research can have implications for quality and innovation in governance and public services so as to accelerate the improvement of West Nias Regency's status as a disadvantaged area